PENGARUH GOOD CORPORATE GOVERNANCE DAN DEBT MATURITY TERHADAP PREDIKSI BOND RATING - Marfuah Marfuah; Hermin Endaryati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
The objective of this study is examine the effect of good corporate governance and debt maturity towards bond rating prediction. Good corporate governance is proxied by institutional ownership, managerial ownership, board size, independent directors, audit committee, and audit quality. The sample in this study consist of 229 bonds issued by financial companies listed on the Indonesia Stock Exchange from 2011 to 2013 and was ranked by PT PEFINDO. This study uses ordinal regression analysis model to test the effect of good corporate governance and debt maturity towards bond rating prediction. The results of this study showed that institutional ownership and audit committee have significant positive effect towards bond rating prediction while independent commissioner have  significant negative effect towards bond rating prediction. Managerial ownership, board size, audit quality and maturity haven’t significantly affect toward bond ratings. The findings of this study indicated that companies with the bigger institutional ownership and the bigger audit committees, then predicted the company has bonds with higher ratings. The findings that the independent commissioner has  significant negative effect toward bond rating prediction indicate that the presence of independent commissioner haven’t been able to role effectively so expected the quality of independent commissioner should be improved.